The Education Office's Strategy for Primary School Mergers - Abdurahman, Abdurahman; Sumarna, Cecep; Sulaiman, Eman; Karim, Abdul; Iskandar, Muhammad (UII Darullughah Waddawah Pasuruan, 2025)
Primary education plays a critical role in building the basic skills required for students' future academic success and social development. This research focuses on strategies for combining primary schools to optimise education services for the community, which previous research has not discussed in terms of local authority. The research method used a qualitative approach of the case study type. Data were collected using interviews, observations and documentation, analysed by reduction, display and conclusion and confirmed through triangulation and depenability. The results of this study illustrate the importance of efficient decision-making strategies for regional education leaders who continue to listen to input from their members, including through swot analysis, optimising services, and meeting future challenges. Contribution of this study is how optimation of esecution of the leader with swot in eraly is giving positive. This research provides a view that local leadership must be able to use its role in updating the state of education so as to create a more qualified and appropriate national education institution.